IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB DAN PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN GAMBUT DI KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Tri Wahyudi Muslim; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to identify the causes and ways of prevention of forest fires and peat in Kempas district Indragiri Hilir Regency based on public perception. This research is a descriptive research. Technique of collecting data of this research are observation, direct interview and questionnaireSampling in this research usingpurposive sampling dan quoted sampling methods.Results of the study of the causes of forest fires and peat that is inKempas district Indragiri Hilir regency based on public perception. The intentional factors are: land clearing by communities and companies by way of burning, conversion of agricultural land to plantation land by burning and land conflicts between communities and companies. Factor of human laxare : burning of plantation waste done by society and negligence of human that cause sparks such as throwing cigarette butts carelessly. The technique the prevention of forest fires and land in Kempas district Indragiri Hilir Regency, based on public perception and knowledge society that is: implement socialization by periodic both directly and indirectly, implementcounselling to the community, the rule of law in a fair and firm for the arsonists, implement the cooperation between all sides of the community, Government and corporate training, implement the opening of the land without burning to the community, the establishment of community groups concerned the joint patrols, fire and Implement of land registration and community land use.Keyword : The cause of fire, The prevention of fire, peatland and forest, Kempas district.